Unilateral biportal endoscopic vs. open surgery in the treatment of young obese patients’ lumbar degenerative diseases: a retrospective study - Ma, Tao; Li, Junyang; Geng, Yongcun; Yan, Dengming; Jiang, Ming; Tu, Xiaoshuang; Chen, Senlin; Wu, Jingwei; Nong, Luming (Frontiers in Surgery, 2024)
BackgroundObesity accelerates the development of lumbar disease and increase the risk during surgery. Unilateral biportal endoscopic discectomy (UBE) is a newly developed minimally invasive technique, which refers to the spinal surgery under unilateral double-channel endoscopic surgery. Therefore, the purpose of this study is whether UBE decompression alone can bring good clinical results to young obese patients with lumbar degenerative diseases.MethodsThe patients with lumbar diseases who underwent UBE and open surgery (open discectomy) in our hospital from February 2020 to February 2022 were selected as young (age ≤ 44 years old) and obesity (BMI ≥ 30 kg/m2). The patients were evaluated with VAS, ODI, JOA and modified Macnab score before operation, 1 month, 6 months and 12 months after operation. Nerve root function sensation, muscle strength and tendon reflex were evaluated. The operation time, estimated blood loss, postoperative hospital stay, incidence of postoperative complications and reoperation rate were recorded. MRI quantitative lumbar multifidus muscle (LMM) comparison was performed 12 months after operation.Results77 patients were included, and the scores of VAS, ODI and JOA were similar in the two groups during the last follow-up. There were no difference in nerve root function sensation, muscle strength or tendon reflex. However, one month after operation, the VAS back score and ODI improvement in the UBE group were significantly better than those in the open group, which were 2.44 ± 0.97, 33.10 ± 6.78 and 2.93 ± 0.79 and 36.13 ± 5.84, respectively, with a statistically significant difference (p = 0.020 and 0.038). According to the modified Macnab criteria, UBE group, the excellent and good rate was 97.2%. The excellent and good rate of open group was 97.6%. The estimated blood loss and postoperative hospital stay in UBE group (36.81 ± 17.81, 3.92 ± 1.32) were significantly better than those in open group (104.88 ± 31.41, 6.41 ± 1.94), with a statistically significant difference (p = 0.010). There was no significant difference in operation time between the two groups (p = 0.070). The number of complications in UBE group was 2 (5.6%) and open group was 4 (9.8%). The fat infiltration rate of 19.3%+11.0% in UBE group was significantly lower than that of 27.0%±13.9% in open group (p = 0.010).ConclusionUBE has the advantage of early recovery in the treatment of lumbar degenerative diseases in young obese patients, and reduces the damage to LMM, so it has a good clinical effect.